Chemical composition, bioactive compounds and antioxidant activity of six avocado cultivars Persea americana Mill. (Lauraceae) grown in Egypt - Rozan, Mahmoud AbdElGelil; Boriy, Esmail Galal; Bayomy, Hala Mahmoud (Emirates Journal of Food and Agriculture, 2021)
Amongst the most common tropical fruits is avocado (Persea americana), which is widely consumed in the world due to its high nutritional value and multiple applications. Hass avocado cultivar is the primary global cultivar of avocado. Recently, some other cultivars are included by some producers in Egypt namely Ettinger, Fuerte, Maluma, Pinkerton, and Reed. The point of the study is to evaluate the chemical composition, fatty acid profile, bioactive compounds, and antioxidant activity of various cultivars in the fruit flesh. The results indicated that the ripening season of avocados extends from early October to mid-March. Ettinger avocado is the earliest cultivar, while the Reed cultivar is the most delayed avocado in the ripening. Hass cultivar recorded a higher value of firmness (89.5 N). Dry matter was 32.12, 27.67% in Hass and Ettinger, respectively. Acidity and chemical composition differed significantly (P <0.05) among all avocados under study. All cultivars can be considered as good sources of K, P, and Mg elements, and moderate sources of Ca and Na elements, while they contain relatively limited quantities of Fe, Zn, and Mn elements. Oleic acid was the main fatty acid present in the oil of all avocado cultivars, while myristic acid was the lowest in all of the cultivars. The acidic amino acids (glutamic and aspartic) were the greatest amino acids in all the studied avocados, while S-amino acids (methionine and cystine) and tryptophane were the lowest acids in the studied cultivars. Hass avocado significantly was the highest in its content of total carotenoids (6.91 μg/g, FW ), α-carotene (0.58 μg/g, FW ), β-carotene (1.43 μg/g, FW ), lutein (3.84 μg/g, FW), total chlorophyll (29.5 μg/g, FW), Chlorophyll a (15.6 μg/g, FW), and Chlorophyll b (13.2 μg/g, FW), total phenols content (4.9±0.38 mg/ g FW), total flavonoids content (0.25±0.01mg/ g FW), Ascorbic acid content (12.8±0.15 mg/ 100g FW), and DPPH value (1.3±0.09 μmol TE/g). The individual phenolic compounds in the flesh of avocado fruits were significantly (P <0.05) affected by cultivars. The major compound was epicatechin, which ranged between 130.12 μg/g DW (in Hass cultivar) and 184.15 μg/g DW (in Pinkerton cultivar).